Fluorous Fullerene Acceptors in Vacuum‐Deposited Photovoltaic Cells. Issue 7 (10th May 2019) - Reeves, Brian J.; Brook, Colin P.; Gerdes, Olga; Deng, Shihu H. M.; Yuan, Qinqin; Wang, Xue-Bin; Strauss, Steven H.; Boltalina, Olga V.; Walzer, Karsten
Abstract : The first successful example of vacuum‐deposited organic photovoltaic (OPV) cells based on a fullerene derivative and a small‐molecule donor is reported. A series of thermally robust fluorous fullerene acceptors with experimental gas‐phase electron affinities ranging from 2.8 to 3.3 eV are paired with a new dicyanovinyl thiophene‐based molecular donor to enable direct comparison of their performance in planar and bulk heterojunction architectures in the cells fabricated by vacuum deposition. Unprecedented insights into the role of the acceptor intrinsic molecular and electronic structures are obtained, which are not obscured by solvent and additive effects as in the typical solution‐processed fullerene‐based OPV cells. Abstract : Organic photovoltaic (OPV) cells are fabricated using thermally robust fluorous fullerene acceptors and a small‐molecule donor via vacuum deposition. A comparative study of planar and bulk heterojunction architectures allows direct probing of effects of acceptor electronic properties on OPV figures of merit, which reveals a surprisingly strong correlation between V oc and experimental gas‐phase electron affinities.